Sosialisasi dan Edukasi Pencegahan Bullying pada Siswa SMPN 1 Junjung Sirih oleh Mahasiswa KKN Universitas Negeri Padang - Al-Ikhlas; Aurel Salbila Putri; Dhimas Tegar Bumi; Jessica Wulandary; Ridho Indra Ardianto; Siraj Beni (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Bullying is a serious problem in school environments with broad impacts on students' mental health and social development. This community service activity was conducted by KKN students from Universitas Negeri Padang at SMPN 1 Junjung Sirih on January 22, 2026, using a participatory educative approach through structured material presentation and interactive discussion. Materials covered the definition, types, impacts, and prevention strategies of bullying. The activity received an enthusiastic response, with students actively engaging in the question-and-answer session. It is recommended that the school integrate bullying education into its regular character development program through collaboration among teachers, parents, and students.